Moving towards a sustainable cetacean-based tourism industry – A case study from Mozambique. (October 2020) - Rocha, Diana; Drakeford, Benjamin; Marley, Sarah A.; Potts, Jonathan; Hale, Michelle; Gullan, Angie
Abstract: Cetacean-Based Tourism (CBT) is often confused with sustainable tourism. However, not every CBT operator has an environmental education component attached to its programme. In reality, CBT has the potential to negatively impact the animals it is targeting; thus management is required to mitigate any harmful effects from tourism activities. This paper analyses the attitudes and perceptions of the marine operators and tourists that partake in dolphin-swim activities in the Ponta do Ouro Partial Marine Reserve (PPMR) in Mozambique. Hand-out questionnaire surveys with closed and Likert scale type questions revealed that the tours are an effective means to promote pro-environmental behaviour and consequently increase compliance with the code of conduct. Nonetheless, in the PPMR, both tourists and operators presented only basic knowledge of the regulations of the reserve and of the dolphin, whale and whale shark code of conduct, indicating that there is a need for improvement. We provide recommendations for improving local management, which are also applicable at the national and international level. Overall, this paper provides knowledge and guidance for moving towards a sustainable based CBT industry in the PPMR. Highlights: Awareness of the Ponta Partial Marine Reserve is high. Tourists' awareness of PPMR regulations and code of conduct for dolphins and whales is low. Operators and tourists have positive attitudes towards PPMR and Code of conduct. Greater outreach on cetacean conservation and PPMR regulations is recommended.